2019
DOI: 10.1002/job.2416
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of (not) seeing eye‐to‐eye about the past: The role of supervisor–team fit in past temporal focus for supervisors' leadership behavior

Abstract: Summary This study seeks to advance our understanding of the leadership consequences that may ensue when supervisors and their teams have similar versus differing orientations toward the past. Integrating a leader–team fit perspective with functional leadership theory, we cast incongruence between supervisor and team past temporal focus as a key antecedent of supervisors' active (i.e., task‐oriented and relationship‐oriented) and passive (i.e., laissez‐faire) leadership behaviors toward the team. We tested our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 103 publications
1
19
0
Order By: Relevance
“…We demonstrate the importance of an individual's temporal focus relative to the temporal focus of important dyadic partners (line managers) and the potential for this to impact resocialization outcomes. In particular, our data illustrate the potential for (in)congruence in temporal focus to impact relational and career related outcomes and contributes to our nascent understanding of temporal focus fit (Briker, Walter and Cole 2020;Waller, Franklin and Parcher 2020). Second, building on recent work on the variant outcomes of past, present and future temporal foci (e.g.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…We demonstrate the importance of an individual's temporal focus relative to the temporal focus of important dyadic partners (line managers) and the potential for this to impact resocialization outcomes. In particular, our data illustrate the potential for (in)congruence in temporal focus to impact relational and career related outcomes and contributes to our nascent understanding of temporal focus fit (Briker, Walter and Cole 2020;Waller, Franklin and Parcher 2020). Second, building on recent work on the variant outcomes of past, present and future temporal foci (e.g.…”
Section: Introductionsupporting
confidence: 54%
“…Furthermore, temporal aspects of team members' personalities may shape managers' evaluations of subordinates (Alipour, Mohammed and Martinez 2017). Moving beyond individual temporal foci, we argue that any mismatches in subjective views of time within teams, or between managers and their teams, may illicit negative reactions that can significantly impact on work outcomes (Briker et al 2020, Eldor et al 2017. Recent evidence (Briker et al, 2020;Waller et al, 2020) suggests that incongruence in temporal focus may be relatively common and points to the need to examine the role of perceived incongruence or misfit in inhibiting team functioning.…”
Section: Theoretical Background Temporal Focus In Workplace Relations...mentioning
confidence: 91%
“…In response to the need for more research on subjective time (e.g., Shipp & Cole, ), this Special Issue offers a set of insightful articles providing new views of time perspective and temporal focus. The first article by Briker, Walter, and Cole () draws on temporal focus, leader–team fit, and theories of leader behavior to specify the leadership implications of a supervisor's temporal focus on the past. Using a sample of 84 supervisors and 296 team members, Briker and colleagues challenge the commonly held assumption that a past temporal focus invariably has negative consequences (e.g., passive leadership).…”
Section: Articles In the Special Issuementioning
confidence: 99%
“…Over the last decade, international research has produced a large number of studies that have shown the importance of temporal focus in various aspects of the lives of individuals, groups and organizations [ 3 5 ]. Some researchers have, for example, investigated temporal aspects related to attitudes [ 6 8 ], motivations [ 9 – 11 ], individual behaviours [ 12 14 ], the effects of time on team processes and performance [ 15 , 16 ], the role of time in organizational and strategic decisions [ 17 19 ] and the dimensions of socio-cultural influence that shape the shared representations of time [ 20 ].…”
Section: Introductionmentioning
confidence: 99%